PENGARUH PERAN FUNGSI INTERNAL AUDIT, PENGALAMAN TERHADAP PEMAHAMAN RISK BASED INTERNAL AUDIT - Ramadhaniyah, Rieka; Pulungan, M.Sadat; Delli, Maria (Journal Accounting International Mount Hope, 2024)
The aim of this research is to prove empirically the influence of the role of the internal audit function on understanding risk based internal audit, as well as experience on understanding risk based internal audit. In this research, the sample studied was 89 employees of the Bandar Lampung Inspectorate. The research is quantitative and analyzed using multiple linear regression. The research results showed that from the T test. The results for The role of the internal audit function with a t value of 3.391 < t table 2.011 and a significance value of 0.001 < 0.05, then the role of the internal audit function has a significant effect on the understanding of risk based internal audit. The Experience variable has a value of tcount 3,112 > ttable 2,011 and a significance value of 0.003 < 0.05, so it can be concluded that experience has a significant effect on understanding risk based internal audit.